Norwegian Rhapsody? The Political Economy Benefits of Regional Integration - Nauro F. Campos; Fabrizio Coricelli; Luigi Moretti (Institute for the Study of Labor (IZA), 2015)
This paper investigates whether joint economic and political integration leads to larger economic benefits than just economic integration. The identification strategy rests on the fact that Norway, at the time of the 1995 Enlargement of the European Union (EU), had successfully completed negotiations and fulfilled all accession requirements, taken membership in the European Economic Area (with full access to the Single Market), but decided in a referendum to reject full-fledged EU membership. Using the differences-in-differences and synthetic control methods with regional data, we find substantial politically driven economic benefits from EU membership: if Norway had joined the EU in 1995, productivity levels between 1995 and 2001 would have been 6% higher on average.
Keywords: C33; F15; F43; O52; 330; political economy benefits; European Union; labor productivity; synthetic counterfactual method; regional data